PID Tuning Of Line Follower Robot Using Android Smartphone - Musaddid, Ahmad Taufiq, Fajar Suryawan, S.T., M.Eng.Sc, Ph.D (2017)
A proportional-integral-derivative (PID) controller is a control strategy commonly used in automation systems. A PID controller calculates an error value continously as the difference between desired setpoint and measured value. PID tuning is a crucial process that is needed in every system that uses PID. Mistuning of PID parameters greatly affects a robot's performance. Hence, PID tuning is a very important step. Moreover, sometimes it is desirable to tune the PID parameters with minimal intrusion to the system. This research aims to produce that minimally invasive procedure by tuning the value of PID wirelessly using android phone via bluetooth. The process of tuning PID is adjusting the proportional, integral, and derivative parameter values. The value of these parameters will be sent by an android phone through bluetooth to the robot system. The robot is controlled by Arduino UNO that receives signals from infrared sensors and then computes the error value. After obtaining the error value, the system then calculates the PID control signal.